Pragmatic education for the development of the Muslim ummah - Hashim, Rosnani (Jamiyah Singapore and ISESCO, 2004)
Seplember 11, 2001 was a watershed in the history 0f Muslim education, not only of world polities. More significanUy, September II led to the scrutiny of lhe madrasa or the traditional system ofIslamic educalion. The United States believes that the militant groups arose from among the followings of leaders who hud a strong affi liation 10 Islam. Consequently, they believe that the root of the problem of terrorism lies in the manner in which rslamic education is taught in IVluslim lands. Once, the IcmljilJad IUld'been used to the advantage of the Americans in the Afghanistan war agai nst the Russian occupation, but 110\¥ that it has been used against them since Septembe r 1L, the Americans believc that thc term should be taken out from the Islamic studies curricldum. In 2002, the International Crisis Group, which is led by Weslern scholars, statesmen and corporate leadcrs conduded a study ofmadrasa in Pakistan. In its report, the Group acknowledged the imporlancc of madrasa education for the society and also proposed the integration of the system into the formal education sector as well as its proper regulation and monitoring. I It was concerned with the provision of job opportunities for the madrasa gradllllies. The US has even used its influence to persuade Saudi Arabia and a few countries in the Middle Fast to revise their Islamic education clllTiculum.2 In addition, it has also lIsed its might and inHucnee to ensure that Ole madrasa W 0 ltld riot breed hatred agai nst the West. "In some places, such as Saudi Arab ia and Kuwait, !he cducation dcbate has focused on how, or whether, the religious cllrrieulum promotes inlolerance and extremism."